2021
DOI: 10.5334/paah.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eccentric Exercise on Skeletal Muscle Injury: From An Ultrastructure Aspect: A Review

Abstract: The contraction of skeletal muscle (SM) plays an important role in providing power for the body to participate in physical activities. Nevertheless, unaccustomed motions, especially eccentric exercises (EE), might cause changes in ultrastructure and mitochondria of SM, increasing potential risks of injuries. The objective of this narrative literature review was to summarize the effects of EE on SM ultrastructure. The results found that EE may lead to changes in the ultrastructure of SM, including the ambiguity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…The hip joint performs a crucial role in lower limb motion, and instability of the hip joint is considered an essential mechanism of lower limb injury [37]. Increased internal and external rotation and internal abduction of the hip joints are associated with patellofemoral pain and iliotibial tract syndrome [38,39]. Our results for the hip sagittal plane PC2 were consistent with previous studies using traditional analysis techniques that reported greater hip flexion and hip ROM for novice runners [11].…”
Section: Discussionsupporting
confidence: 88%
“…The hip joint performs a crucial role in lower limb motion, and instability of the hip joint is considered an essential mechanism of lower limb injury [37]. Increased internal and external rotation and internal abduction of the hip joints are associated with patellofemoral pain and iliotibial tract syndrome [38,39]. Our results for the hip sagittal plane PC2 were consistent with previous studies using traditional analysis techniques that reported greater hip flexion and hip ROM for novice runners [11].…”
Section: Discussionsupporting
confidence: 88%
“…By summarizing, we can affirm that the method proposed here could be positively exploited during training sessions since it only requires: (i) the execution of easy motor tasks typical of training programs, since their correct execution is shown to be correlate to the prevention of ACL injury [ 65 , 66 ] and (ii) the use of only one low-cost wearable inertial sensor, which has already been demonstrated to be useful for the assessment of ACL injury [ 67 ]. Using this protocol as a screening method, customized interventions could be implemented for the athletes identified as potentially at higher risk of injury.…”
Section: Discussionmentioning
confidence: 80%
“…Excessive ROS produced by strenuous exercise may cause exercise fatigue by reducing the release of skeletal muscle sarcoplasmic reticulum Ca 2+ and/or the sensitivity of myofibrils Ca 2+ [34]. However, under mild oxidative stress induced by physical exercise, the S-glutathionization of troponin can improve contractile apparatus Ca 2+ sensitivity in fast-twitch fibers, thereby delaying the occurrence of fatigue [35].…”
Section: Skeletal Muscle Fatiguementioning
confidence: 99%